A Case Report of Cannabis Induced Hemoptysis - Hashmi, Hafiz Rizwan Talib (Medicine (Baltimore), 2016)
As the principal route of marijuana use is by inhalation, potential harmful consequences on pulmonary structure and function can be anticipated. Here, we present a case of hemoptysis attributed to smoking cannabis in a 38-year-old man. The patient experienced an episode of hemoptysis and shortness of breath immediately after smoking marijuana. Chest radiograph and computed tomography (CT) scans of the chest showed bilateral diffuse ground-glass opacities. A fiber optic bronchoscopy confirmed bilateral diffuse bleeding from respiratory tract. Additional evaluation of hemoptysis indicated no infection or immunological responses. Urine toxicology was positive for cannabis. Chronic marijuana smoking causes visible and microscopic injury to the larger airways responsible for symptoms or chronic bronchitis. We review the beneficial and deleterious effects of marijuana and describe a case of significant hemoptysis attributed to smoking marijuana. In addition to other respiratory complications of marijuana use, physicians should educate their patients about this potentially lethal effect of marijuana smoking in the form of hemoptysis.